Application Of The Dynamic Increasing Energy Test (DIET) In Load Transfer Analysis Of Precast Piles Driven In Soft Clay Formation - Jean Balech (Deep Foundations Institute, 2002)
This paper presents some results of dynamic loading tests performed on concrete piles driven in soft clay formation. The load transfer mechanism, measured in the dynamic increasing energy test (DIET), under blows of growing energy, is described in terms of mobilized normal forces diagrams and unitary local friction and displacements. It was observed that the lateral skin friction grows up to a maximum, in the soft clay layer and, gradually diminishes to a residual value when the system presents the maximum mobilized resistance. It may be concluded that the rupture load is not equal to the maximum mobilized point resistance plus the maximum mobilized local friction as suggested by most of static bearing capacity formulae.